Introduction: The Role of AI in Transforming Management Research - Iis Azelya; Sergei A. Filin (PT Agung Media Publisher, 2025)
Artificial intelligence (AI) is revolutionizing management research by enabling more efficient data analysis, decision-making, and operational workflows. However, its application also raises questions about its transformative role and implications for academic writing in this field. A systematic review of literature published over the past decade was conducted to evaluate the applications, benefits, and challenges of AI in management research. Emphasis was placed on identifying key tools and technologies, along with their impacts on research quality and efficiency. Findings reveal that AI significantly enhances research by automating data handling, improving predictive accuracy, reducing biases, and streamlining academic writing processes. Despite these advancements, challenges such as ethical concerns and the need for human oversight persist. This study highlights the importance of balancing AI implementation with human judgment to ensure ethical practices and effective utilization. It addresses gaps in existing research and emphasizes AI's transformative potential in management studies. AI plays a pivotal role in enhancing the quality and efficiency of management research, but its integration requires careful consideration to maximize its benefits while mitigating potential drawbacks.